2020
DOI: 10.3390/agronomy10101493
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic Fungal Endophyte Colletotrichum tofieldiae Ct0861 Colonizes and Increases Growth and Yield of Maize and Tomato Plants

Abstract: Facing rising global food demand in a sustainable way is a great challenge of modern agriculture. Thus, the increase of crop productivity and resilience in an adverse climate scenario is urgently needed. Fungal endophytes have been described as potential biological tools to improve plant yield and tolerance to biotic and abiotic stresses; however, their application in agriculture needs further research. The fungal endophyte Colletotrichum tofieldiae strain Ct0861 establishes a mutualistic interaction with Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 87 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…Presence of these taxa may indicate higher carbon sequestration in intercropping plots that is enhanced by the perennial intercropping system (Cong et al 2015). Other enriched fungi genera likely confer more distinct ecosystem services, such as forming mycorrhizal (Ravnskov et al 2006;) and endophytic associations with plant roots that promote plant growth activities through increased nutrient supply (Díaz-González et al 2020;Macías-Rubalcava et al 2008;Munasinghe et al 2017). The fungi may also directly or indirectly stimulate production of beneficial secondary metabolites and protection against pathogens and insect pests (Hiruma et al 2016;Zin and Badaluddin 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Presence of these taxa may indicate higher carbon sequestration in intercropping plots that is enhanced by the perennial intercropping system (Cong et al 2015). Other enriched fungi genera likely confer more distinct ecosystem services, such as forming mycorrhizal (Ravnskov et al 2006;) and endophytic associations with plant roots that promote plant growth activities through increased nutrient supply (Díaz-González et al 2020;Macías-Rubalcava et al 2008;Munasinghe et al 2017). The fungi may also directly or indirectly stimulate production of beneficial secondary metabolites and protection against pathogens and insect pests (Hiruma et al 2016;Zin and Badaluddin 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth promotion by C . tofieldiae was also observed in tomato and maize, although the mechanism of growth promotion remained unclear (Díaz‐González et al ., 2020). Further, the question remains how non‐Brassicaceae plants that should be devoid of IG biosynthetic enzymes are capable of maintaining a beneficial relationship with C .…”
Section: The Role Of the Psr In Other Beneficial Plant–fungal Associa...mentioning
confidence: 99%
“…Colletotrichum tofieldiae is an endophytic fungus of A. thaliana that has been widely studied as a promoter of plant growth through an increase in the plant content of P in deficiency situations (Hiruma et al 2016). Its application in crops such as tomato or maize has reported a significant promotion of plant growth and yield, although it cannot yet be confirmed that the same mechanisms described in A. thaliana are involved (Díaz-González et al, 2020).…”
Section: Plant-phosphorus Uptakementioning
confidence: 99%